Impact of early benefit assessment on patients with epilepsy in Germany: Current healthcare provision and therapeutic needs - Strzelczyk, Adam; Hamer, Hajo (Der Nervenarzt, 2016)
Epilepsy is one of the most common chronic neurological diseases and represents a significant burden for patients, their families and society. In more than 75 % of patients anticonvulsant therapy consists of valproate, carbamazepine, lamotrigine or levetiracetam. There is a need for polytherapy in drug-refractory patients and they suffer from negative effects on quality of life and employment that is associated with high indirect costs. To allow a comprehensive treatment in this patient group, access to new anticonvulsants with novel modes of action is needed; however, all applications for new antiepileptic drugs failed to prove added benefits during the Pharmaceutical Market Restructuring Act (AMNOG) in Germany. One of the main reasons is the mandatory definition of a standard comparative therapy. It remains unclear whether there will be studies in the future which will fulfill the requirements of the current version of AMNOG. Observational studies after approval and marketing of new antiepileptic drugs could be better alternatives to prove added benefits for individual patients in the current German healthcare system.
EVALuna2:22465